Реалната хералдика во Македонија до 1991 - Real Heraldry in Macedonia until 1991 - Jonovski, Jovan (Македонски хералд - Macedonian Herald, 2021)
Every European region and country has heraldry with some specifics. In this paper we will consider the real heraldry in the Peoples/Socialist Republic of Macedonia, understood by the multitude of the coat of arms, and the armorial knowledge and art. It covers the earliest preserved heraldic motifs and coat of arms found in Macedonia in pre-Ottoman period. Also, real heraldry that existed on the territory as well as the State and municipal heraldry of the P/S R Macedonia. The paper covers the development of heraldry as both a discipline and science and the development of heraldic thought in SR Macedonia until its independence in 1991.